1994
DOI: 10.2337/diacare.17.8.828
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Hemoglobin in Diabetic Patients

Abstract: Level of HbF is increased (> 1.0%) among 7.5% of unselected diabetic patients. In adult (> or = 15 years) diabetic patients, it is increased among 6.5%, which is 3.4 times more often than in the control population. Acute hematological conditions or malignancies do not explain the difference. Elevated HbF seems to be associated with type I diabetes and insulin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
2
14
1
Order By: Relevance
“…Moreover, we have observed that a decrease in HbA1c levels, and thus a better metabolic control, induced by intensive treatment in type 1 and type 2 diabetes subjects is associated with a decrease in HbF levels. An increased prevalence of high HbF levels ranging from 13 to 38% of cases has been reported in type 1 diabetes subjects (6)(7)(8). Our data are in agreement with these reports.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, we have observed that a decrease in HbA1c levels, and thus a better metabolic control, induced by intensive treatment in type 1 and type 2 diabetes subjects is associated with a decrease in HbF levels. An increased prevalence of high HbF levels ranging from 13 to 38% of cases has been reported in type 1 diabetes subjects (6)(7)(8). Our data are in agreement with these reports.…”
Section: Discussionsupporting
confidence: 83%
“…It has been suggested that high HbF levels could be related to a direct effect of insulin therapy (7,12). However, our data do not agree with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that have examined differences by ethnicity have found significant variation in rates of medical insurance coverage (42). Other studies of patients with diabetes have found that most have some form of medical insurance and that African Americans and non-Hispanic whites have similar rates of coverage (43).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators suggested that increased prevalence of elevated HbF may be associated with poor glycemic control [7,8]. On the other hand, another group of researchers reported that no significant differences were observed in glycemic control and the duration of diabetes between patients with high or low HbF levels [9]. …”
Section: Introductionmentioning
confidence: 99%